Optimized Replacement T4 and T4+T3 Dosing in Male and Female Hypothyroid Patients With Different BMIs Using a Personalized Mechanistic Model of Thyroid Hormone Regulation Dynamics - Cruz-Loya, Mauricio; Chu, Benjamin B.; Jonklaas, Jacqueline; Schneider, David F.; DiStefano, Joseph (Frontiers in Endocrinology, 2022)
Objective A personalized simulation tool p-THYROSIM was developed: (1) to better optimize replacement LT4 and LT4+LT3 dosing for hypothyroid patients, based on individual hormone levels, BMIs and gender; and (2) to better understand how gender and BMI impact thyroid hormone dynamical regulation over time in these patients. Methods p-THYROSIM was developed by (1) modifying and refining THYROSIM, an established physiologically-based mechanistic model of the system regulating serum T3, T4 and TSH level dynamics; (2) incorporating sex and BMI of individual patients into the model; and (3) quantifying it with 3 experimental data sets and validating it with a fourth containing data from distinct male and female patients across a wide range of BMIs. For validation, we compared our optimized predictions with previously published results on optimized LT4 monotherapies. We also optimized combination T3+T4 dosing and computed unmeasured residual thyroid function (RTF) across a wide range of BMIs from male and female patient data. Results Compared with 3 other dosing methods, the accuracy of p-THYROSIM optimized dosages for LT4 monotherapy was better overall (53 vs. 44, 43 and 38%) and for extreme BMI patients (63 vs. 51% low BMI, 48 vs. 36 & 22 for high BMI). Optimal dosing for combination LT4+LT3 therapy and unmeasured RTFs were predictively computed with p-THYROSIM for males and females in low, normal and high BMI ranges, yielding daily T3 doses of 5 to 7.5 μg T3 combined with 62.5–100 μg LT4 for women or 75–125 μg LT4 for men. Also, graphs of steady state serum T3, T4 and TSH concentrations vs RTF (range 0-50%) for untreated patients showed that neither BMI nor gender had any effect on RTF predictions for our patient cohort data. Notably, the graphs provide a means for estimating unmeasurable RTFs for individual patients from their hormone measurements before treatment. Conclusions p-THYROSIM can provide accurate monotherapies for male and female hypothyroid patients, personalized with their BMIs. Where combination therapy is warranted, our results predict that not much LT3 is needed in addition to LT4 to restore euthyroid levels, suggesting opportunities for further research exploring combination therapy with lower T3 doses and slow-releasing T3 formulations.